Correlation between Serum Magnesium and Calcium Level in Children with Idiopathic Nephrotic Syndrome during Nephrosis - Chaudhury, Gulshan Nigar; Hanif, Mohammed; Afroz, Mahenaz; Begum, Dilruba (Bangladesh Journal of Child Health, 2017)
Background: Biochemical alteration is a common phenomenon in all kidney disease including nephrotic syndrome (NS). Objective: To evaluate the magnesium (Mg) level in patients with nephrotic syndrome and its relation to calcium. Methods: In this observational cross sectional study,we measured serum magnesium and serum calcium levels in children with nephrotic syndrome.It was conducted in the Department of Pediatrics, Dhaka Shishu(children) Hospital, Dhaka, from January 2015 to June 2015. A total of fifty four diagnosed cases of nephrotic syndrome were divided into initial episode, first relapse,infrequent relapse and frequent relapse. Mean level of serum magnesium and calcium of all four groups were then compared. Results :The mean level of serum magnesium during initial episode was 2.28±0.36mg/ dl and it was 2.04±0.29,2.06±0.29 and 1.76±0.32mg/dl during first relapse, infrequent relapse and frequent relapse respectively. The mean serum magnesium level in different patterns of nephrotic syndrome was found to be statistically significant. Hypomagnesemia was mostly found in frequent relapse nephrotic syndrome patients. The mean level of serum calcium during initial episode was 2.01±0.16 and it was 1.98±0.17,2.06±0.13 and 2.05±0.15 during first relapse, infrequent relapse and frequent relapse respectively. The mean serum calcium level in different patterns of nephrotic syndrome was found to be statistically insignificant. There was no significant corelation between calcium level with magnesium level (r = -0.08, p = 0.28). Conclusion: Hypomagnesemia is commonly found in frequent relapse nephrotic syndrome. There was no significant correlation between calcium with magnesium level. Bangladesh J Child Health 2016; VOL 40 (3) :139-143